Perancangan Sistem Informasi Mentoring untuk Perguruan Tinggi - Reina Reina; Irma Irawati Ibrahim; Josef Bernadi Gautama (Bina Nusantara University, 2013)
Mentoring supports the success of student’s study in almost all colleges. Mentoring activities include consulting, mentoring and enrichment materials, and monitoring the achievement of study for all students. Along with the growing number of students, encountered several obstacles in the process of mentoring such as the limitations of time and place to hold mentoring, the availability schedule given by the mentor, and the inadequate number of mentors. Research methods used include field studies, literary studies, problem identification, and problem analysis. To provide appropriate solutions in response to the existing problems, an information system of mentoring is designed.